Papel da microbiota disbiótica no metabolismo de triptofano pelo hospedeiro e seu impacto na infecção pulmonar por pseudomonas aeruginosa - Camila Bernardo de Brito (2022)
Pseudomonas aeruginosa is an opportunistic microorganism that affects mainly hospitalized patients who previously used broad spectrum antimicrobials. Prolonged use of antimicrobials is associated with changes in intestinal and systemic levels of metabolites produced by the intestinal microbiota, including tryptophan metabolites. Tryptophan is an essential amino acid supplied by diet. It is catabolized by the intestinal microbiota to indole derivatives, and by the host, generating kynurenines among other catabolites, through the activity of the indoleamine-2,3-dioxygenase 1 (IDO1) enzyme. These catabolites are agonists of the aromatic hydrocarbon receptor (AHR), which exerts various immunomodulatory functions. The aim of this study is to evaluate whether intestinal dysbiosis alters tryptophan metabolism and if this metabolic shift plays any role in the susceptibility to pulmonary infection by Pseudomonas aeruginosa. For this, we induced dysbiosis in wild type (WT) and mice deficient for the IDO1 enzyme (IDO1-/- ) or for the AHR receptor (AHR-/- ) with an antimicrobial cocktail for 14 days, when animals were inoculated intranasally with P. aeruginosa (PAO1 or PA103 strains). Mice that received antimicrobials had intestinal dysbiosis with reduced total bacteria, including indole-producing bacteria. Dysbiosis was accompanied by increased serum tryptophan concentration and decreased kynurenine concentration, indicating a change in tryptophan metabolism. Furthermore, infected dysbiotic mice showed higher lethality rates when compared to eubiotic mice, as well as higher bacterial load in the bronchoalveolar lavage (BAL). Also, dysbiotic mice presented increased in kynurenine amounts in the lung after infection. Interestingly, dysbiosis was able to induce increased AHR expression and activation. Using an AHR antagonist and AHR knockout mice we observed that the absence of AHR activation in dysbiotic animals resulted in lower bacterial load when compared to dysbiotic animals that received vehicle. Interestingly, IDO1-/- mice or animals treated with an IDO1 inhibitor were resistant to infection even after induction of dysbiosis. Thus, it can be concluded that dysbiosis resulting from prolonged antimicrobial treatment interferes with tryptophan metabolism, resulting in greater susceptibility to P. aeruginosa infection. This increased susceptibility of dysbiotic animals is associated with increased IDO1 enzyme activity, heightened kynurenine accumulation and greater AHR receptor activation, disrupting Pseudomonas aeruginosa phagocytosis